Table of Content - - (Journal of engineering sciences and information technology, 2025)
Table of Content:1. The Role of the ChatGPT AI Application in Enhancing the Performance of Computer Trainers  at the Technical College in MeccaEng. Sami Munahi Al-Meqati2. The Effect of Iron Slag Powder Addition on the Performance of Self-Compacting Concretelecturer \ Haifa Ali Abu Haliga, Abdul Hadi Mohamed Alebrahim, Hamed Munir Al-Mobaid3. Large Language Models in Intellectual Discourse: An Empirical Evaluation of PerformanceDev \ Abdennacer Elbasri
Keywords: Journal of Engineering Sciences and Information Technology